The Methodological Framework for the Study of Nostalgic and Personal Narratives - Ivan Kovačević (University of Belgrade, 2016)
Nostalgic narratives occur in two major forms – as historical nostalgia and as personal nostalgia. Personal contents and historical stories can be registered in the free form of life stories, a well-known genre in folkloristics, as well as in narratives obtained through two forms of interview. The first form of interview is generated from anthropological tradition, or rather, ethnographic data gathering and refers to descriptions of social, economic and all other elements of the past, while the other form of interview, generated in psychology, similar to an in-depth interview, refers to personal experiences from an earlier time. When nostalgic narratives are collected using either of these two approaches, it is possible to a) conduct an analysis of each narrative on its own, or b) compare them in order to determine similarities and differences. Based on this it is possible to determine where and how descriptions of the past which do not coincide with personal experience are generated, which is the main characteristic of both yugonostalgia and other similar ways of remembering the past.